Chlorpyrifos should be banned in agriculture and livestock production in Colombia - Villar, David; Schaeffer, David J. (Revista Colombiana de Ciencias Pecuarias, 2022)
Chlorpyrifos (CPF) is a pesticide widely used in Colombia´s agriculture, including crops, farm animals and pets, despite it has been banned for use in the European Union and the United States. Studies demonstrate that even low blood levels of CPF -which do not inhibit blood acetylcholinesterase- can lead to child developmental and neurological disorders such as smaller head circumference and brain alterations, and psychomotor and cognitive deficits related to learning ability, attention and memory. In adults, CPF is an endocrine disruptor and breast carcinogen. High direct and indirect economic costs have been associated with CPF exposure. Not only farmers and their families -who have the highest exposures- but the general population consuming crops sprayed with CPF are also at risk. For these reasons CPF was recently banned by the European Union (2020) and the USA (2021). Pesticide regulation policies vary greatly depending on which and how scientific studies are used to assess health risks. Pesticide evaluations funded by the chemical industry should be rectified to avoid conflicts of interest. Furthermore, political alignment with the interests of the industry should not take precedence over independent scientific evidence. It is discouraging, to say the least, that until stricter health laws are passed in Colombia, CPFs and related pesticides will continue to be imported from those countries that have already banned them. Colombian scientists should raise their voice to challenge blind acceptance of profits over unintended consequences, and efforts to prevent pesticide´s abuse should be encouraged.